Fifteen-second bouts of hyperoxia improve 5-minute time-trial performance in acute hypoxic conditions - Martin Faulhaber; Sina Schneider; Linda K. Rausch; Tobias Dünnwald; Verena Menz; Hannes Gatterer; Michael D. Kennedy; Wolfgang Schobersberger (Current Issues in Sport Science)
Introduction